−2/9−(−1/3÷3/5) ,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,

Respuesta :

Answer:

Step-by-step explanation:

[tex] \\ \sf \frac{ - 2}{9} - ( \frac{ - 1}{3} \div \frac{3}{5}) [/tex]

[tex] \\ \sf = \frac{ - 2}{9} - ( \frac{ - 1}{3} \times \frac{5}{3} )[/tex]

[tex] \\ \sf = \frac{ - 2}{9} - \frac{ (- 5)}{9} [/tex]

[tex] \\ \sf = \frac{ - 2}{9} + \frac{5}{9} [/tex]

[tex] \\ \sf = \frac{ - 2 + 5}{9} [/tex]

[tex] \\ \sf = \frac{3}{9} [/tex]

[tex] \\ \sf = \frac{1}{3} [/tex]